Bank management - Koch, Timothy W. (Dryden Press, 1995)
The management and regulatory environment of commercial banks has seen rapid change in recent years. This modern introduction to commercial bank management is the most current in the market and reflects changes during the last year that competing books do not. Excellent and complete coverage focuses on bank management problems now and in the 21st Century in a way that helps students apply financial concepts to a variety of credit, investment, and funding decisions.